2014
DOI: 10.1089/thy.2013.0150
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performances of Various Gray-Scale, Color Doppler, and Contrast-Enhanced Ultrasonography Findings in Predicting Malignant Thyroid Nodules

Abstract: The ring enhancement and homogeneity of enhancement of thyroid nodules on CEUS and the microcalcification and halo on GSUS were the four most valuable indicators in the differential diagnosis of thyroid nodules. Conjoint analysis of specific features of thyroid nodules on GSUS and CEUS could enhance the diagnostic value of thyroid nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 23 publications
5
69
0
3
Order By: Relevance
“…According to our data, the most reliable symptom of benignity was the rim-like enhancement presenting 94% sensitivity, 61% specificity, and 77% accuracy. In accordance with our results, also in studies by Zhang et al (2010), Cantisani et al (2013) and Ma et al (2014) rim-like enhancement is specific to benign nodules. Results yielded by Zhang et al (2010) showed 94.1% specificity, 83.0% sensitivity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to our data, the most reliable symptom of benignity was the rim-like enhancement presenting 94% sensitivity, 61% specificity, and 77% accuracy. In accordance with our results, also in studies by Zhang et al (2010), Cantisani et al (2013) and Ma et al (2014) rim-like enhancement is specific to benign nodules. Results yielded by Zhang et al (2010) showed 94.1% specificity, 83.0% sensitivity.…”
Section: Discussionsupporting
confidence: 93%
“…The results are ambiguous and sometimes contradictory. The diagnostic value of CEUS has been analysed in only very few studies (Ferrari et al, 2008;Zhang et al, 2010;Nemec et al, 2012;Cantisani et al, 2013;Giusti et al, 2013;Deng et al, 2014;Ma et al, 2014), yielding variable results; the sensitivity varies between 68-100% and specificity -between 67-594%.…”
Section: Introductionmentioning
confidence: 99%
“…An important indicator predicting benign nodules was ring enhancement of contrast due to a complete capsule around the nodule. Consistent with the results of our study, Ma et al, Zhang et al, and Jiang et al observed ring enhancement as a predictor of benign thyroid nodules [20,[31][32][33].…”
Section: Variablessupporting
confidence: 93%
“…Numerous studies have reported several gray-scale ultrasound parameters associated with thyroid cancer (Table 4) [7][8][9][20][21][22][23][24][25]. In the current study, the strongest conventional feature predictive for malignancy was Type-IV/V power Doppler pattern with sensitivity 78.7%, specificity 90.2%, PPV 93.4%, NPV, 71.7% and accuracy 85.3%, followed by microcalcifications and irregular margins.…”
Section: Discussionmentioning
confidence: 53%
“…It has found widespread application in many organs, such as the liver, gall bladder, and kidney. Its use in assessing diseases of the thyroid gland has been the subject of a number of reports, although its precise role remains uncertain [1316]. ACE/AME/ETA (American Association of Clinical Endocrinologists/Associazione Medici Endocrinology/European Thyroid Association) guidelines in 2010 state that contrast agents provide only ancillary data for the diagnosis of malignant thyroid nodules and offer only a modest improvement over the information obtained with traditional color Doppler or power Doppler examinations, and that the use of US contrast agents should be restricted to defining the size of necrotic areas in lesions after US-guided ablation procedures [17].…”
Section: Introductionmentioning
confidence: 99%